Modeling Tsunami Induced Debris Impacts on Bridge Structures using the Material Point Method. (2017) - Yang, Wen-Chia; Shekhar, Krishnendu; Arduino, Pedro; Mackenzie-Helnwein, Peter; Miller, Greg
Abstract: Bridges represent a key part of infrastructure, playing a critical role in emergency response and post-event reconstruction. In this context, it is important for bridges to be able to survive both ground shaking and the effects of tsunamis. This paper focuses on numerically modeling bridge loading due to tsunamis. Although several studies have addressed the effect tsunami loads on bridges, few have examined the influence of debris carried by the tsunami. These problems involve complex contact interactions between solids and fluids that are not easily accommodated using typical fluid-oriented or solids-oriented numerical frameworks. In this paper the material point method (MPM) is used to address fluid and solid (moving and stationary) interactions with emphasis in evaluating demands on bridge superstructures by tsunami-driven debris. Two parametric studies have been conducted in this study. The first is aimed at understanding the influence of the contact area and the eccentricity of impact on the impact forces. The results show that the effect of these two factors are reduced with an increase in longitudinal length of the solid object. The second part of the study tries to evaluate the difference between tsunami driven debris impact loads and in-air debris impact loads. The results indicate that tsunami driven debris impacts tend to be larger by upto 35% compared to only in-air impact forces calculated using empirical equations.